The first two-fold interpenetrating polyoxometalate-based coordination polymer with helical channels: structure and catalytic activities. Issue 2 (8th December 2015) - Sha, Jing-Quan; Sun, Long-Jiang; Zhu, Pei-Pei; Jiang, Jianzhuang
Abstract : A polyoxometalate-based coordination polymer POMCP-1 with a [helix + interpenetration] double configuration was successfully isolated, which shows effective catalytic activities for the esterification reaction and the photodecomposition of Rhodamine-B. Abstract : A polyoxometalate-based coordination polymer with a [helix + interpenetration] double configuration feature, Na[Ag4 (pyttz-I)2 ][H2 PMo12 O40 ] (POMCP-1 ), was isolated and structurally characterized. POMCP-1 exhibits a 3D structure with open 3D tunnels along the [10−1], [111] and [1−11] axes. The large void space in the single net induces the interpenetration of two identical 3D frameworks, resulting in the formation of a highly ordered two-fold interpenetrating aggregate. To the best of our knowledge, this represents the first example of two-fold interpenetrating POMCPs with helical channels. In particular, POMCP-1 was found to display efficient catalytic activities for the esterification reaction and the photodecomposition of Rhodamine-B.